Majaz dalam Puisi Al-Masa' Karya Khalil Mutran - Ni'ma Royyin Husnaya; Mardjoko Idris (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2024)
This research discusses the majaz language style found in the poem Al-Masa>' by Khalil Mutra>n. This research is library research with a descriptive qualitative approach. This research aims to describe the form of majaz found in poetry and the relationship (alaqah) between the meaning of the majazi and the essence of the majaz. In this poem, Mutra>n uses a lot of majaz, namely terms that are not interpreted in their proper meaning. so that many terms are not intended with the lexical meaning of the lafadz (hakiki>), but the poet wants another meaning (majazi>) with a specific purpose. The results of the research show that poets use a lot of uslub majaz. Some of the majaz uslubs found in this poem include majaz aqli> in the form of referring fi'il to fa>'il which is not real, majaz mursal with halaqah juz'iyyah, haliyah, mahaliyah, and jasaliyah, and isti'arah tashrihiyyah and tamtsiliyyah.